Probiotics and Bacteriocins Against SARS-CoV-2: Therapeutic Frontiers and Mechanistic Insights - Simeng Sun; Xinyue Guo; Simeng Liu; Shuhong Wu; Lei Ma; Hongru Yang (Probiotics and Antimicrobial Proteins, 2026)

Genetic Variants in EMT-Related lncRNAs Modulate the Risk of Colorectal Cancer in the Chinese Population - Simeng Gu; Zhaohui Zhang; Keyi Cheng; Aibuta Yeerken; Sangni Qian; Fanjia Guo; Mingjuan Jin; Kun Chen (Biochemical Genetics, 2026)

Efficient removal of perchlorate by a quaternary ammonium-functionalized hydrogel: Performance and mechanisms - Yongkang Guo; Simeng Xia; Zhou Shi; Lin Deng; Haojie Zhang (Journal of Environmental Chemical Engineering, 2026)

Reduction of As(V)-bearing goethite by dissolved organic matter from arsenic-prone groundwater during the repeated electron shuttling - Xiaojun Feng; Zhengqi Su; Simeng Li; Xiaoxing Ming; Di Zhang; Huaming Guo (Journal of Hazardous Materials, 2026)

Genome-wide identification of oat EIL gene family and analysis of expression patterns under abiotic stress - Xiaodong Guo; Xuanyu Liu; Jiaming Nie; Qidi Zhang; Simeng Cai; Huiyan Liu; Bing Han; Hongbin Zhao (Genetic Resources and Crop Evolution, 2026)

Long-term scenarios for climate adaptation of cotton crops in China, considering multidimensional biophysical and socio-economic scenario analysis - Simeng Guo; Fengqi Wu; Yuhan Wang; Jian Wang; Zhenggui Zhang; Zhanlei Pan; Chenxi Chong; Pengcheng Li; Weibin Huang; Guilan Sun; Xin Li; Shuchen Wang; et al. (Journal of Cleaner Production, 2026)

Deep eutectic solvents molecular interfacial engineering for suppressing chemical corrosion in Li metal batteries - Simeng Wang; Hongtao Li; Caiwen Zhao; Pengtao Guo; Minting Luo; Yu Liang; Jiajia Huang; Shimou Chen (Chemical Engineering Journal, 2025)

Surface hydroxyl-driven =FeOFe(II)+ and =FeOH2+ generation on polyphenol-modified ZVI: Mechanistic insights into Cr(VI) and surface passivation layer removal - Shilin Shi; Chi Zhang; Simeng Guo; Lu Yang; Yuwei Pan; Minghua Zhou; Ying Zhang (Journal of Hazardous Materials, 2025)

Design of a recombinant Pseudomonas strain with enhanced degradation viability towards catecholic compounds by reconstituting EDO-hydrolysis pathway - Zihao Huang; Yingdan Piao; Xiemuxinuer Abuduwupuer; Simeng Ding; Tian Chen; Song Jiang; Yiqi Ding; Zheng Guo; Renjun Gao (Journal of Environmental Chemical Engineering, 2025)

Ligand exchange by As(V) enhanced desferrioxamine B-induced goethite dissolution: Insights into As mobilization in groundwater systems - Simeng Li; Wei Xiu; Xin Liu; Zhixin Fang; Jonathan R. Lloyd; Huaming Guo (Applied Geochemistry, 2025)

Metabolome genome-wide association analyses identify a splice mutation in AADAT affects lysine degradation in duck skeletal muscle - Dapeng Liu; Wenlei Fan; Youyou Yang; Zhanbao Guo; Yaxi Xu; Jian Hu; Tong Liu; Simeng Yu; He Zhang; Jing Tang; Shuisheng Hou; Zhengkui Zhou (Science China Life Sciences, 2025)

Tracing the carbon footprint of cotton garments from seed to garment: Evidence from an empirical study of multiple sites in China - Shuchen Wang; Chenxi Chong; Weibin Huang; Simeng Guo; Yuhan Wang; Yaopeng Zhang; Zhanlei Pan; Jian Wang; Xin Li; Wenqi Zhao; Zhenggui Zhang; Zhanbiao Wang (Resources, Conservation and Recycling, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Contribution of plastic solid components to volatile organic compounds formation during plastics combustion - Xinglei Wang; Simeng Tang; Ling Ding; Xinran Qiu; Zhenming Zhang; Li Xu; Xujun Liang; Xianfei Huang; Xuetao Guo (Journal of Hazardous Materials, 2024)

Engineering PD-L1 targeted liposomal canagliflozin achieves multimodal synergistic cancer therapy - Simeng Wang; Mengjun Sui; Quan Chen; Jiahua Guo; Huini Yang; Ye Zhou; Meiju Ji; Yangyang Cheng; Peng Hou (Chemical Engineering Journal, 2024)

One-step rapid removal of Cu(II) complexes via dual-active-site MOF catalysis with Peroxymonosulfate: Cooperative oxidation and adsorption - Shuo Wang; Simeng Guo; Xuedong Du; Ziqian Liu; Yujia Yang; Yaran Song; Qingrui Zhang (Chemical Engineering Journal, 2024)

Thyroglobulin as a Sensitive Biomarker of Iodine Status in Mildly and Moderately Iodine-Deficient Pregnant Women - Yujie Jiang; Simeng Gu; Zhe Mo; Xueqing Li; Chenyang Liu; Yahui Li; Guangming Mao; Yuanyang Wang; Fanjia Guo; Xiaoming Lou; Xiaofeng Wang (Biological Trace Element Research, 2024)
Pregnant women are more susceptible to iodine deficiency. However, there are limitations in existing indicators for the evaluation of iodine nutrition in pregnant women. The study aimed to explore whether thyroglobulin (Tg) can be used as a more sensitive biomarker for pregnant women with mild and moderate iodine deficiency. A repeated-measure study was conducted among 1332 pregnant women in Zhejiang Province, China. Serum and urine specimens were collected at a mean of 10, 17, and 32 weeks of pregnancy, respectively; thyroid-stimulating hormone (TSH), Tg, and urinary iodine concentrations were measured. Linear mixed effects models were used to determine the associations between interaction of iodine concentrations and increasing gestation week and TSH and Tg, where participants were divided by urinary iodine concentration (UIC). The median Tg concentration was 11.56, 11.45, and 12.43 μg/L in the first, second, and third trimesters, respectively. After controlling the covariates, the interaction effects between the iodine status and gestation week were significant for both TSH and Tg ( p = 0.038 and p = 0.007, respectively). TSH increased with the week of gestation in both iodine concentration groups. Tg increased with advancing pregnancy in the iodine-deficient group whereas it did not in the iodine-sufficient group. There was no significant variation in TSH at each trimester, and Tg was higher in the iodine-deficient group than in the iodine-sufficient group. Tg may be a more sensitive iodine status biomarker than TSH for pregnant women with mild-to-moderate iodine insufficiency.

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

The abundance and pathogenicity of microbes in automobile air conditioning filters across the typical cities of China and Europe - Kaifei Su; Zhishu Liang; Simeng Zhang; Wen Liao; Jianwei Gu; Yunlong Guo; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2024)

Quantifying physiological contributions to yield loss in response to planting date in short-season cotton under a cotton wheat double-cropping system - Simeng Guo; Yingchun Han; Guoping Wang; Fengqi Wu; Yaoyu Jia; Jiale Chen; Xiaofei Li; Wenli Du; Yabing Li; Lu Feng (European Journal of Agronomy, 2024)

An ultrasensitive and specific ratiometric electrochemical biosensor based on SRCA-CRISPR/Cas12a system for detection of Salmonella in food - Simeng Zheng; Qian Yang; Haoyu Yang; Yunzhe Zhang; Wei Guo; Wei Zhang (Food Control, 2023)

Changes in within-boll yield components explain cotton yield and quality variation across planting dates under a double cropping system of cotton-wheat - Simeng Guo; Taijie Liu; Yingchun Han; Guoping Wang; Wenli Du; Fengqi Wu; Yabing Li; Lu Feng (Field Crops Research, 2023)

Application of Al-Fe Co-modified Rice-Straw Biochar to Fluoride Removal: Synthesis, Optimization, and Performance - Chaoshuo Hou; Wei Xiu; Huaming Guo; Simeng Li; Chunping Jiang (Water, Air, & Soil Pollution, 2023)

FRZB1 rs2242070 polymorphisms is associated with brick tea type skeletal fluorosis in Kazakhs, but not in Tibetans, China - Yanmei Yang; Qiaoshi Zhao; Yang Liu; Xiaona Liu; Yanru Chu; Huazhu Yan; Yumei Fan; Simeng Huo; Limei Wang; Qun Lou; Ning Guo; Dianjun Sun; et al. (Archives of Toxicology, 2018)

Erratum to: The role of particle size of glyburide crystals in improving its oral absorption - Wenqian Yang; Yongjun Wang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

The role of particle size of glyburide crystals in improving its oral absorption - Yongjun Wang; Wenqian Yang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)